Alcohol hangover versus dehydration revisited: The effect of drinking water to prevent or alleviate the alcohol hangover - Mackus, Marlou; Stock, Ann-Kathrin; Garssen, Johan; Scholey, Andrew; Verster, Joris C (Elsevier Inc., 2024)
The alcohol hangover is a combination of negative mental and physical symptoms which can be experienced after a single episode of alcohol consumption, starting when blood alcohol concentration (BAC) approaches zero. A popular theory suggests that dehydration is the primary cause of alcohol hangover and that the consumption of water could alleviate hangover symptoms. Here, the current evidence on the relationship between hangover severity, thirst, and water consumption is summarized. The positive correlations of the amount of water consumed with both hangover severity and thirst suggest that both dehydration and the hangover are co-occurring after-effects of alcohol consumption. While hangovers were typically relatively enduring, dehydration effects were usually mild and short-lasting. Survey data revealed that water consumption during or directly after alcohol consumption had only a modest effect in preventing next-day hangover. Also, the amount of water consumed during hangover was not related to changes of hangover severity and thirst. Thus, water consumption was not effective to alleviate the alcohol hangover. Taken together, these data suggests that alcohol hangover and dehydration are two co-occurring but independent consequences of alcohol consumption.
Keywords: Alcohol; dehydration; hangover; inflammation; thirst; water consumption; Health(social science); Biochemistry; Toxicology; Neurology; Behavioral Neuroscience